(untitled) (International Journal of Engineering Materials and Manufacture, 2020)
Failures of two power take off (PTO) shafts of an aircraft have been analysed. Two shafts, one each developed by two different manufacturers failed separately during power run endurance test conducted at room temperature and ambient normal atmosphere. In both the cases, cracks were observed on the outer diaphragm disc. One shaft showed cracking in the engine side, while the other one exhibited cracks in the aircraft mounting accessory gearbox (AMAGB) side. Chemical analysis, microstructure and hardness evaluation indicate that the diaphragm material of the shafts is Ti-6Al-4V alloy used in solution treated and aged condition, as per the desired specification AMS 4928. Microstructural in-homogeneity, possibly a result of improper forging, was observed in diaphragm material of both the shafts. Additionally, surface discontinuities induced by forging and subsequent insufficient machining were noticed on the diaphragms. The diaphragms failed by fatigue with cracks possibly nucleating at surface discontinuities. Discontinuities with lower availability in one shaft led to somewhat increased life (466 million cycles) as compared to the life (104 million cycles) of the other shaft. Another possible factor contributing to lower life in the later shaft is the presence of higher quantity of nitrogen rich inclusions. Controlling factor triggering the failure of diaphragm of shaft with lower life seems to be the available high stress level along the rim periphery, while that for shaft with higher life is presence of few localized sharp surface discontinuities.